The Use of Blended Learning Based Flipped Classroom towards Students’ Reading Comprehension Achievement and Perspectives - Ardiansyah, Welly; Aryanti, Nurul; Lestari, Pratiwi (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The study conducted a profound exploration on the potential impacts of a blended learning-based flipped classroom method on students' reading comprehension and their perception towards it. The methodology used a quantitative quasi-experimental approach with purposive sampling in a state senior high school in Palembang. The process of collecting data involved the utilization of questionnaires, post-tests, and pre-tests. Either experimental and control class has 25 students. The test's reliability and validity were thoroughly examined through the employment of the Split-Half technique as well as the Aiken formula. Furthermore, in an effort to establish dependability for the questionnaire, Pearson Correlation testing methods were utilized. A comprehensive data analysis covered broad statistical areas including application of Shapiro-Wilk procedure, Levene Statistics test evaluating homogeneity characteristics, deployment of independent samples t-test and incorporation of Cohen's d in hypothesis validation procedures. Post intervention results from experimental group significantly indicated marked improvements in reading comprehension following hypothesis assessment. The alternative hypothesis (Ha) was thereby substantiated, leading to the rejection of the null hypothesis (H0). Additionally, students perceive the blended learning-based flipped classroom as an enjoyable teaching approach that enhances their engagement in the learning process and aids improvement in areas that require attention. These findings imply that implementing the blended learning-based flipped classroom could be a valuable resource for English teachers, offering advantages to students such as improved accessibility and readiness for reading comprehension learning.